Biolaw and Bioethics: a long, shared journey (Revista Iberoamericana de Bioética, 2017)
The author focuses on the relationship between bioethics and biolaw over the course of their long, shared journey. Despite their mutual enrichment, problems have arisen with boundaries and the tendency to develop ethical issues as if they were legal ones. The article analyzes how human rights have served as a leading source and frame of reference for bioethical discourse, how bioethics advisory commissions have driven international law in the field of biomedicine, and the development of a Constitutional Law of the bioethical citizen as a response to researchers and scientists (biocrats), specifically in the development of certain rights related to the human genome.
Keywords: Bioethics; biolaw; bioethics commissions; human genome